2016
DOI: 10.1007/s00417-016-3375-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring choriocapillaris under reticular pseudodrusen using OCT-Angiography

Abstract: OCT-A reveals a distinct reduction in CC vessel density and CC decorrelation signal index in eyes affected by RPD, which emphasizes the relevance of the CC layer in RPD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 43 publications
(58 reference statements)
11
80
0
2
Order By: Relevance
“…CC OCTA in Early/Intermediate AMD Our group reported for the first time significantly reduced CC vessel density and reduced CC flow in eyes with reticular pseudodrusen (RPD) compared with healthy control eyes, suggesting a CC functional compromise in RPD eyes [28]. Later, Nesper et al [40] confirmed these results using an OCTA metric for CC nonperfusion.…”
Section: Octa In Dry Amdmentioning
confidence: 83%
See 2 more Smart Citations
“…CC OCTA in Early/Intermediate AMD Our group reported for the first time significantly reduced CC vessel density and reduced CC flow in eyes with reticular pseudodrusen (RPD) compared with healthy control eyes, suggesting a CC functional compromise in RPD eyes [28]. Later, Nesper et al [40] confirmed these results using an OCTA metric for CC nonperfusion.…”
Section: Octa In Dry Amdmentioning
confidence: 83%
“…This can produce artifacts, but allows for a more robust visualization of vasculature [26]. The exact localization and thickness of the CC slab vary between 0 and 34 µm below the RPE/Bruch's membrane reference and between 4.4 and 30 µm, respectively, depending on the device used [17,20,27,28]. Notably, manufacturers use various definitions of the CC slab level, and not all of them offer a presetting for CC examination yet (Table 1).…”
Section: Heidelberg Spectralismentioning
confidence: 99%
See 1 more Smart Citation
“…CC decorrelation signal index was defined as the average decorrelation value of all pixels in the en face CC angiogram [8,16] . This method has been described previously [17] and must not be confused with other methods described in the literature [18,19] . The OCT-A scans on both devices were performed consecutively within a few minutes in between to eliminate the potential effects of diurnal variation [20] .…”
Section: Imaging and Image Analysismentioning
confidence: 99%
“…A previous OCT-A study based on the SSADA showed a comparable variability between the first and the second CC measurements. The included subjects in that study were distinctly older [17] . Pechauer et al [16] also reported a similar variability when assessing the peripapillary retinal flow index in healthy subjects also using the SSA-DA.…”
Section: Intra-device Variabilitymentioning
confidence: 99%